Systemic Immune-Inflammation Index As Predictor Factor Of Neoadjuvant Chemotherapy Response In Locally Advanced Breast Cancer At Dr. Soetomo General Hospital - Dinal Muhammadi, Asdi Wihandono, and Marjono Dwi Wibowo (South Eastern European Journal of Public Health, 2025)
Background: Breast cancer is the most prevalent malignancy and the leading cause of death among women, both in developed and developing countries. At Dr. Soetomo Hospital, 77% of patients present at an advanced stage. Immuno-inflammatory cells play an important role in tumorigenesis and cancer progression. Objective: This study is an analytical study examining the role of the systemic immune-inflammation index (SII) as a prognostic factor in patients with locally advanced breast cancer undergoing neoadjuvant chemotherapy at Dr. Soetomo General Hospital, Surabaya. Methods: In this study, SII values were measured using data from complete blood count (CBC) and differential leukocyte count laboratory tests. SII values were obtained by calculating the NLR multiplied by the platelet count in units of 10⁹ cells/L of blood fluid. Results: The SII values in this study sample varied within a range of 247 to 2306, with a mean value of 820.2 ± 448.3. Using a cut-off point of 900 to determine high or low SII groups, 36.1% of the samples had a high SII value (≥900), while the remaining 63.9% had a low SII value (<900). Conclusion: SII (Systemic Immune-Inflammation Index) has a significant relationship with the response to neoadjuvant chemotherapy in patients with locally advanced breast cancer. The use of SII as a predictive biomarker can assist in optimizing therapeutic strategies and patient monitoring.